Measuring Resilience in the Context of Conflict-Related Sexual Violence: A Novel Application of the Adult Resilience Measure (ARM). Issue 19 (October 2022) - Clark, Janine Natalya; Jefferies, Philip; Foley, Sarah; Ungar, Michael
There is a rich body of research addressing the issues of conflict-related sexual violence, and a similar wealth of scholarship focused on resilience. To date, however, these literatures have rarely engaged with each other. This article developed from an ongoing research project that seeks to address this gap, by exploring how victims-/survivors of conflict-related sexual violence in three highly diverse settings – Bosnia-Herzegovina, Colombia and Uganda – demonstrate resilience. This research is the first to apply the Adult Resilience Measure (ARM), a 28-item scale that seeks to measure protective resources across individual, relational, and contextual subscales, to the context of conflict-related sexual violence. A total of 449 female and male participants in the three aforementioned countries completed the ARM (in the framework of the study questionnaire) as part of this research. This article presents some of the results of the analyses. Specifically, we first sought to establish through Confirmatory Factor Analysis whether the ARM was actually measuring the same construct in all three countries, by confirming the invariance (or otherwise) of the factor structure. The second aim was to explore how different resources function and cluster in different cultural contexts, to arrive at a more nuanced understanding of the different protective factors in the lives of study participants. We generated different factor structures for BiH, Colombia, and Uganda respectively, suggesting that a single factor structure does not sufficiently capture the diverse groupings of protective factors linked to the particularities of each country, including the dynamics of the conflicts themselves. Ultimately, we use the findings to underscore the need for policy approaches that move away from a deficit model and give greater attention to strengthening and investing in the (often overlooked) protective resources that victims-/survivors may already have in their everyday lives.